Interest Rate Swaps and Corporate Financing Choices. - Titman, Sheridan (Journal of Finance, 1992)
This paper describes the firm's decision to borrow short- term versus long-term and shows how the introduction of interest rate swaps affects this choice. The model shows that in the absence of a swap market, interest rate uncertainty can lead firms to substitute long-term for short-term financing. However, when swaps exist, there is a tendency for firms that expect their credit quality to improve to borrow short-term and use swaps to hedge interest rate risk. The model suggests that, while the demand for fixed for floating swaps is enhanced, the demand for floating for fixed swaps is reduced by the presence of asymmetric information.